CFD simulation of hydrodynamics and concentration polarization in osmotically assisted reverse osmosis membrane systems - Chong, Y. K.; Fletcher, D. F.; Liang, Y. Y. (Elsevier, 2024)
Osmotically assisted reverse osmosis (OARO) has been recently suggested as an alternative to improve water recovery of reverse osmosis (RO) for applications in which RO has reached its limit. To elucidate the physics, a computational fluid dynamics (CFD) methodology is developed that describes all important physical phenomena occurring in the feed, porous and draw sides of OARO. The CFD model shows good agreement with the reported experimental data and predicts the water flux better than a simplified analytical model. This paper reveals that external concentration polarization (ECP) at the feed side is more important than internal concentration polarization (ICP) within the porous support layer, especially for a system with a high transmembrane pressure, Δp (≥40 bar). In contrast to conventional RO, where concentration polarization (CP) at the permeate side is negligible, OARO experiences a non-negligible ECP at the draw (permeate) side, particularly in cases with high Δp. This analysis also found that both counter-current and co-current configurations show similar flux performance at module scale.